Finding the place of the artisan in developing Woodstock - Simos, Christos (School of Architecture, Planning and Geomatics, 2018)
Argument - The relationship between Cape Town and its socio-economic change has resulted in developments often disassociated with immediate context ,but rather following capitalist ideals with very little to no variation. This results in social alienation of existing communities with the new developments. These new developments are internalized enclave models with no engagement to their edge conditions but in the case of Woodstock, are selected solely for their proximity to the city center and their low start-up cost. These developments are also restricted to the measures of the urban scale and take a place in the morphology of the city by creating a new dialogue and place. However they do add value to the city and initiate a flurry of similar developments around them using the basic model of the enclave. In this dissertation I propose the existence of a hybrid model that lies between syntactic values learnt from enclaves of malls and the armatures of the main street/s. By engaging with examples like the biscuit mill and Woodstock exchange and looking into their syntactic structure in comparison to the structure of dedicated malls (such as canal walk), I will be able to construct a set of design characteristics from which I can propose a new spatial model. This together with a critical look at the two main roads (Victoria road and Albert road) that run through Woodstock there will be enough local research into the overall form of the two contrasting models. Question - Dealing with an existing urban fabric which has undergone many infrastructural changes over the past 40 years, the new model of the enclave takes on a new form in Woodstock yet is bound by the spatial parameters of the existing morphology. The question of how much how much can we change something without losing its original value whilst working within its limitations? Locating the design intervention - Based on the theoretical research into enclaves and armatures, I isolate "anchors" which facilitate the function of an enclave and act as the main attractors of people. Naturally spaces form around these "anchors" and a series of linear paths leading up to them. In the case of Woodstock I have chosen the Woodstock station, and its adjacent site. The main intervention is this site and its structures climaxing at the stations entrance. The initial diagrams are a series of models and sketches which explore the path/ sand structures supporting this movement. The programme itself builds off the tradition of artisans and craftsmen of the area which manufacture, market and sell in the same space. Tectonics are derived from the typology of the buildings found on site and are tailored related to the artisans who will use these spaces. The existing structure contributes to the overall expression and is explored as an adaptable spatial model. Conclusion - Describing a new model is context dependant and the theory serves as a guiding set of rules which are used to establish the argument. Breaking of these rules creates the new but must be critically analysed for is values or its shortcomings.